THE EFFECT OF TEACHING MEDIA AND VOCABULARY MASTERY ON STUDENTS’ SPEAKING SKILL (Experiment at the Tenth Grade of State Senior High School in Tasikmalaya-West Java) - Yudi Kurniadi (INFERENCE: Journal of English Language Teaching, 2018)
The aims of this research are to find 1) the interaction effect of teaching media and vocabulary mastery on the students’ speaking skill. 2) the effect of teaching media on students’ speaking skill, 3) the effect of vocabulary mastery on students’ speaking skill, The research methodology used is experiment. The sample size of 72 students which consists of 36 for experiment class and 36 for control class, and the sampling technique used is cluster sampling. Data collection is obtained by testing their vocabulary mastery and speaking skill. Data analysis is using descriptive statistics, normality test, homogeneity test, and two ways ANOVA to test hypothesis testing. The research results conclude 1) there is no significant interaction effect of teaching media and vocabulary jointly on student’s speaking skill. This is proved by the results of significance value (sig) is 0.450 and Fo = 0.577. Because Sig.=0.450 > 0.05, then Ho is accepted and H1 is rejected. 2) There is a significant effect of teaching media on students’ speaking skill. This is proved by the result of significance value (sig) is 0.000 and Fo = 16.236. Because Sig.=0.000 < 0.05, then Ho is rejected and H1 is accepted, 3) There is a significant effect of vocabulary mastery on student’s speaking skill. This is proved by the result of significance value (sig) is 0.001 and Fo= 11.770. Because Sig.=0.001 < 0.05), then Ho is rejected and H1 is accepted. Keywords: Teaching Media, Vocabulary Mastery, Speaking Skill